Recharging ground water from a brick lined farm canal (1: 1 slope) under shallow water table condition as affected by distance and time - Goyal, V.; Jhorar, B.S.; Malik, R.S. (Annals of Agricultural Research, 2016)
The study was conducted in the year 2006-07 to quantify the field groundwater recharge dynamics due to seepage from a brick lined farm canal. Rise in water table on the onset of canal was observed in observation wells which were kept at an orthogonal distances of X = 10, 20, 40 and 60 m from a 25 years old brick lined canal at different time intervals. The initial water table was at 2.88 m depth from soil surface. The height of the bottom of the farm canal (Ho ) from the water table was 2.77 m. Groundwater rise increased with time at all orthogonal distances and followed the square root time law with r2 values more than 0. Groundwater rise rate decreased with time following inverse square root law with r2 value equals to 0.9402 for X = 10m. Seepage from farm canal was mainly a horizontal infiltration phenomenon under shallow water table condition. The groundwater rise decreased with distance exponentially with r2 value more than 0.99. The practical implication is that lined farm canal contributes to considerable seepage and groundwater recharge and it could be an effective and ecofriendly measure for groundwater recharge in falling water table situations.